Development of Bulk Packaging and Storage of Shallot (Allium Ascalonium) Puree - Ahmad, Noor Azizah (2008)
The present trend where modern housewives have limited time in preparing food and also the food industry and services need ingredients in convenience form in order to cut down extensive labour, has led to the increase of ready to use food ingredient . With this in mind, ready to use shallots (Allium ascalonium) is able to satisfy the needs of retail and institutional consumers. Studies on physico-chemical changes, microbiological test and sensory evaluation for development of processing treatments of shallot puree using mild heat and acidification were carried out. The L value (L*) and hue angle (Hab) of shallot puree increased significantly (p<0.05) during 8 weeks storage at 5±1°C (85-95% RH), whilst, the chroma value (C*) decreased significantly (p<0.05). Total plate count (TPC) slowly increased during storage period in all samples. The yeast and mould count increased in both acidified and control samples, whilst, the increment of coliforms was only detected in control sample. However, the mean scores on colour, odour and overall acceptability decreased significantly (p<0.05) during storage period for all samples. Total soluble solid (TSS) and pH value slowly decreased during storage period. Sample that was acidified + heated could be kept for 8 weeks at 5±1°C (85-95% RH) followed by 7 weeks for acidified sample. The shelf life of less than 2 weeks was obtained for both heated and control samples. The optimal conditions of modified atmosphere storage were investigated, in order to provide a basis for the development of modified atmosphere packs for shallot puree. Qualities of shallot puree were tested at different atmospheric condition (with or without S, 10, 15 and 20% CO₂) and temperatures (5, 15 and 25) ±1°C by using Ony/LLDPE and PET/PE/A1/PE as packaging materials. The carbon dioxide content in shallot puree packed with Ony/LLDPE decreased significantly (p<0.05) for all treatments during 12 weeks of storage, whilst the oxygen content increased significantly (p<0.05). The L value (L*) and hue angle (Hat,) showed significant (p<0.05) increased in all samples: However, the chroma value (C*) and organoleptic evaluation decreased significantly (p<0.05) throughout the storage period. TPC and Lactobacillus spp. count increased slowly during storage period in all samples. However, the population of coliform, yeast and mould count and Pseudomonas spp. count were undetected in all samples. The pH value and TSS decreased significantly (p<0.05) in shallot puree packed with different carbon dioxide contents and packaging materials during storage period. Shallot puree packed in Ony/LLDPE with 10% carbon dioxide was found to be the best treatment for extending the storage life up to 12 weeks at 5±1°C (85-95% RH). The quality changes of shallot puree stored at 10 % C02 and packed in OnylLLDPE was studied in bulk form through out storage. There was a significant (p<0.05) increase in the L value (L *) and hue angle (Bab) but not in chroma value (C*) (p<0.05) for both treatments. There is a highly significant decrease (p<0.05) in sugar (fiuctose, glucose and sucrose) content of shallot puree throughout storage, whilst, total sugar showed no significant (p>0.05) difference between treatments during storage. Volatile oil of shallot puree contained sulphur group as major compounds. TPC and Lactobacillus spp. count gradually increased until the end of storage period.